2007
DOI: 10.1159/000107491
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Therapeutic Index of Tension-Free Vaginal Tape and Transobturator Tape for Stress Urinary Incontinence

Abstract: Background/Aims: The aim of this study was to obtain the surgical therapeutic index (STI) of tension-free vaginal tape (TVT) and transobturator tape (TOT) and compare it with the previously obtained result of Burch colposuspension. Methods: The study population consisted of 121 patients who were diagnosed as having stress urinary incontinence, underwent TVT or TOT between January 1, 2000 and June 30, 2005 and were followed up for at least 1 year. Patients with detrusor overactivity, urinary tract infection, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(23 reference statements)
0
4
1
Order By: Relevance
“…The analysis divided by treatment showed that, at 1 year of follow-up, TVT-O was effective in 83% of patients and TVT in 100% of them in the short-term (p<0.001), different to previous literature data that showed similar cure rates among techniques [17,[24][25][31][32], but almost similar to the study of O'Connor and colleagues that found an overall cure rates of 77% for TVT-O [33]. Furthermore, the subgroup analysis of SUI severity showed that all patients insufficiently cured were affected by SUI2 and treated with TVT-O (only 66% cured), while the others (SUI1/TVT-O and SUI1-2/TVT patients) had 100% cure rates.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The analysis divided by treatment showed that, at 1 year of follow-up, TVT-O was effective in 83% of patients and TVT in 100% of them in the short-term (p<0.001), different to previous literature data that showed similar cure rates among techniques [17,[24][25][31][32], but almost similar to the study of O'Connor and colleagues that found an overall cure rates of 77% for TVT-O [33]. Furthermore, the subgroup analysis of SUI severity showed that all patients insufficiently cured were affected by SUI2 and treated with TVT-O (only 66% cured), while the others (SUI1/TVT-O and SUI1-2/TVT patients) had 100% cure rates.…”
Section: Discussioncontrasting
confidence: 78%
“…All studies that directly compared them found similar results in terms of cure [17,[24][25][31][32], and three of them also found important differences for the occurrence of postoperative complications [17,[31][32]. A recent meta-analysis confirmed similar positive results among techniques, although commented that "the poor quality of most of the studies, both in terms of methodology and clinical parameters, limited the strengths of the recommendations..." [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[16] However, some studies have shown that low MUCP and/or VLPP were associated with increased failure with the transobturator route. [11][17] [18] [19] [20] [21]Schierlitz et al randomized women with poor urethral function (MUCP ≤ 20 cm H20 and /or delta VLPP of ≤ 60 cm/H20) to retropubic or transobturator procedures. [22]Postoperative USI at 6 months was less in the retropubic (21%) than the transobturator groups (45%) ( p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…9,261 In addition, the qualifiers persistent or de novo 261 were often used. De novo OAB, indicating the occurrence of OAB after sling surgery, was reported in 0-48% of patients in various studies (REFS 17,18,20,26,39,(46)(47)(48)(50)(51)(52)(53)55,(57)(58)(59)61,62,66,67,70,(73)(74)(75)(76)(77)79,83,87,88,91,92,96,97,99,140,152,153,155,157,159,161,163,164,(166)(167)(168)(170)(171)…”
Section: Oab Symptomsmentioning
confidence: 99%